AKM effects for German labour market data from 1985 to 2021 - Benjamin Lochner; Stefanie Wolter; Stefan Seth (Journal of Economics and Statistics, 2024)
This article describes the processing and accessibility of the person and establishment fixed wage effects in German administrative data. These effects have been estimated following the approach of Abowd, J., Kramarz, F., and Margolis, D. (1999. High wage workers and high wage firms. Econometrica 67: 251-333) and Card, D., Heining, J., and Kline, P. (2013. Workplace heterogeneity and the rise of West German wage inequality. Q. J. Econ. 128: 967-1015). They can be linked to most of the available administrative datasets provided by the Research Data Center (FDZ) of the German Federal Employment Agency at the Institute for Employment Research (IAB). They are available for different time intervals from 1985 until 2021. These effects have been used in numerous articles that deal with the contributions of workers and establishments to earnings inequality.
Keywords: J31; J62; C23; 330; AKM; German administrative microdata; labour market data; wages; worker and firm fixed effects